2018
DOI: 10.20945/2359-3997000000062
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25-hydroxy vitamin D levels are associated with aggressive breast cancer variants and poor prognostic factors in patients with breast carcinoma

Abstract: Objective: This study was conducted to assess the serum 25-hydroxy (OH) vitamin D levels in patients with breast cancer compared to healthy controls and to identify its association with aggressive breast cancer phenotypes. Materials and methods: Serum 25-OH vitamin D levels of 78 breast cancer patients and 78 matched healthy controls were estimated using ELISA. The cases and controls were matched with respect to age, menopausal status, parity, weight, height and co-morbidities. Prognostic factors like grade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…Another case control study in Asian women also suggests potential preventive effect of vitamin D on breast cancer for Korean women [57]. Similar findings of protective role of vitamin D against breast cancer are reported from studies in Indian populations [52,58]. Two studies done in Pakistan have only descriptive analysis in one [59] and small sample size in the other study [60].…”
Section: Introductionsupporting
confidence: 57%
“…Another case control study in Asian women also suggests potential preventive effect of vitamin D on breast cancer for Korean women [57]. Similar findings of protective role of vitamin D against breast cancer are reported from studies in Indian populations [52,58]. Two studies done in Pakistan have only descriptive analysis in one [59] and small sample size in the other study [60].…”
Section: Introductionsupporting
confidence: 57%
“…6 Another study referred by Arunkumar Karthikayan et al concluded that low level of 25(OH)D in women was associated with aggressive breast cancer phenotypes. 34 According to a case control study an inverse relationship existed between breast carcinoma and serum vitamin D level that was taken after breast cancer diagnosis but different results were obtained in a prospective study where measurements were taken long before diagnosis. 29 A case control study held in Dow University Hospital in 2017 revealed that vitamin D levels were lower in breast cancer patients (85.7%) as compared to healthy females (55.8%).…”
Section: Resultsmentioning
confidence: 99%
“…The role of vitamin D in tumour differentiation is well established in colon and breast cancer. It has been found that poorly differentiated cancers have a lower level of vitamin D compared to well-differentiated variants in colon and breast malignancies [ 32 , 33 ]. Studies have proven that there is a significant difference in the expression of vitamin D receptors and vitamin D deficiency between premalignant and malignant gastric cancer cells [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%